Oral Presentations' Anxiety among Egyptian Undergraduates: Causes and Remedies - Morsi, Wesam Khairy; Zaki, Mission M. (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
One of the goals, in education is to help students improve their communication and social skills to prepare them for participation in society and successful careers worldwide. This explains why oral presentations have become a method of evaluation in higher education institutions to enhance students’ ability to communicate effectively. However, many students who are learning English as a foreign language often feel anxious when they have to speak. The aim of this paper is to explore and discuss the factors that impact the performance of Egyptian undergraduate students during presentations, as well as suggest strategies to help them overcome their fear of speaking in a foreign language. This study is exploratory, non-experimental in which ninety-nine undergraduate EFL learners responded to survey questions. Analysis of the research findings indicated that anxiety stems from sources such as the fear of being judged, making errors, lack of practice, and other significant factors. The research also proposed strategies for students to manage their anxiety while presenting orally.